Diseño de un sistema de sujeción para los elementos neumáticos fijos del laboratorio de neumática de la UAN (2020)
This project was carried out in order to implement the fixed elements found in the benches of the pneumatics laboratory of the Antonio Nariño University, to use them in a modular way in the vertical bench found in the laboratory, designing a modular system of quick coupling for the fixed pneumatic elements that are available in the banks, the parameters were determined, the system plans were viewed and elaborated taking into account the morphology, safety, material and cost. The heaviest element was obtained and it exerted the greatest force at the time of carrying out a laboratory practice. The Taiyo brand double-acting cylinder found in the vertical bench of the Antonio Nariño University laboratory was used as a reference. For the development of the work, two software will be used: Excel version 2016, managing data and analysis for the design of the spring, Visual Basic, diagrams and data manipulation and the CAD software SolidWorks version 2018, the design, assembly and simulation of movement of pieces. The clamping system designed with a spring mechanism, found the cylinder advance force of 98.17 N and the recoil force of 82.47 N, taking into account the area of the cylinder and the pressure of the system being this of 2 bars, by The free-body diagram identifies the forces acting on the system and obtains the required force that the spring must generate, capable of counteracting the force produced by the cylinder advance. Based on measurements taken using a caliper and taking into account the specifications of the vertical bench and pneumatic elements, ergonomics, selection of construction elements, material, ease of assembly and disassembly, adaptation of the pneumatic elements, designed the fully modular quick coupling clamping system.